Anaerobic co-digestion for oily-biological sludge with sugarcane bagasse for biogas production under mesophilic condition - Ghaleb, A.A.S. (IOP Publishing Ltd, 2020)
The oily-biological sludge is one of the toxic organic sludge generated from petroleum oil refineries wastewater treatment plants. However, its low Carbon/Nitrogen ratio (C/N) need a co-substrate material to meet the requirement of anaerobic digestion process C/N. The oily-biological sludge can act as a substrate and inoculum at the same time. Sugarcane bagasse is an organic waste and has high C/N ratio. Therefore, it is a proper material which can balance the batch C/N ratio. In this study, three mixing ratios for both materials with C/N ratios 20.0, 25.10 and 30.0 respectively. The temperature, mixing and digestion duration were 37 Â°C, 60 rpm and 33 days respectively. Both materials were pre-treated under thermo-chemical conditions to increase biogas yeild. The maximum biogas yield was for the maximum C/N and co-substrate/inoculum ratios with 9,268 mL. Â© 2020 Institute of Physics Publishing. All rights reserved.